(untitled) (Research, Society and Development, 2024)
Nosemosis is one of the main diseases of bees, caused by microsporidia of the genus Vairimorpha (Nosema). The main etiologic agents are Vairimorpha apis and Vairimorpha ceranae. These pathogens are widely distributed around the world, and in Brazil, they have already been reported in some states, but these data have never been gathered in a review. The objective of this study was to perform a systematic review of the occurrence and distribution of the microsporidium Vairimorpha spp. in apiaries in Brazil. The search was done in the SciELO, PubMed, DOAJ, and Capes Journals (Scopus) databases. 14 articles were selected and published in English and Portuguese. In the included publications, only eight Brazilian states were referred (Bahia, Espírito Santo, Goiás, Minas Gerais, Piauí, Rio Grande do Sul, Santa Catarina, and São Paulo). No work was conducted in the northern of the country, and most of the publications are concentrated in the southern and southeastern. Regarding the Vairimorpha species, only V. apis and V. ceranae were investigated, and V. ceranae was predominantly detected. Most of the studies were done only with the Africanized bee Apis mellifera. This review showed which Brazilian regions have never been explored in terms of incidence and distribution of these pathogens, revealing a gap to be filled by the country’s beekeeping surveillance and health systems. In addition, because of the great Brazilian biodiversity, it is evident that the occurrence and distribution of these pathogens also need to be investigated with other bee species.